ВИКОРИСТАННЯ АКТИВНИХ МЕТОДІВ НАВЧАННЯ В СИСТЕМІ ПІДГОТОВКИ СПЕЦІАЛІСТІВ З ЕКОНОМІКИ (Педагогіка вищої та середньої школи, 2022)
Methodology of a framing game is consiolered. This article deals with the question of formation of student creative abilities. The author shows the specific conditions to form student’s creative abilities at schools of higher learning.